Brooks Range Treeline White Spruce Branch Primary Growth (2019-2022) ... - Sullivan, Patrick; Hewitt, Rebecca; Maher, Colin; Dial, Roman (NSF Arctic Data Center, 2023)
Measurements of treeline white spruce annual branch primary growth during 2019, 2020, 2021 and 2022. Measurements were made using digital calipers on branches at breast height with persistent apical dominance. The purpose of of this dataset was to examine spatial variation in treeline white spruce branch growth across the Brooks Range and in relation to local microclimates. ...